Endocarditis following Consumption of Cereal Associated with Salmonella enterica Subtype Mbandaka Outbreak - Jana K. Dickter; LiYing Cai; David S. Snyder (Case Reports in Infectious Diseases)
A 69-year-old immunocompromised man developed mitral valve endocarditis due to Salmonella enterica serotype Mbandaka, contracted from the cereal outbreak. The patient had a history of HLA-matched related hematopoietic stem cell transplant with persistent graft-versus-host disease (GVHD). This case report discusses prior international outbreaks that occurred due to Salmonella enterica subtype Mbandaka, the risks of developing endovascular infections from salmonellosis, and persistent infections that may develop more frequently with S. enterica serotype Mbandaka. The patient received a six-week course of intravenous antibiotics and remains on oral suppressive antibiotics, with his length of therapy to be determined based on his GVHD treatment.